1996
DOI: 10.1152/ajpendo.1996.271.2.e261
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between sleep quality and glucose regulation in normal humans

Abstract: To define the effects of sleep on glucose regulation, we analyzed plasma glucose levels, insulin secretion rates (ISR), and plasma growth hormone and cortisol levels in normal subjects receiving a constant glucose infusion during nocturnal sleep, nocturnal sleep deprivation, and daytime recovery sleep. Plasma glucose and ISR markedly increased during early nocturnal sleep and returned to presleep levels during late sleep. These changes in glucose and ISR appeared to reflect the predominance of slow-wave (SW) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
96
0
2

Year Published

1998
1998
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(101 citation statements)
references
References 22 publications
3
96
0
2
Order By: Relevance
“…CONCLUSIONS -This long-term study supports the hypothesis, based on earlier experimental research, that sleep problems are associated with alterations in metabolic variables, with glucose intolerance, and with type 2 diabetes (11,12,23). At the same time, our study expands the earlier findings by showing that sleep disturbances are able to predict future diabetes in middle-aged men.…”
Section: Independent Predictors Of Diabetes At Follow-upsupporting
confidence: 89%
“…CONCLUSIONS -This long-term study supports the hypothesis, based on earlier experimental research, that sleep problems are associated with alterations in metabolic variables, with glucose intolerance, and with type 2 diabetes (11,12,23). At the same time, our study expands the earlier findings by showing that sleep disturbances are able to predict future diabetes in middle-aged men.…”
Section: Independent Predictors Of Diabetes At Follow-upsupporting
confidence: 89%
“…Furthermore, six hours before baseline determination, they had the same light meal containing 20% of theoretic energy need. Finally, in the present study the subjects were not allowed to sleep, which permitted the assessment of the effect of the diurnal cycle and food intake, independently of sleep related metabolic changes 23 ± some of which may affect leptin levels. 24 In the present study, the circadian cycle was demonstrated by cortisol changes, and the lack of sleep-related hormonal disturbances by the absence of sleep-related growth hormone peak (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…[10,11] By contrast, sleep dysfunction is linked to the development of physical and psychological issues including cardiovascular problems, diabetes, obesity, anxiety, and all-cause high rates of death [12] and number of studies have supported that the metabolic rate related to interference of normal sleep behaviors may related to the development of obesity, cardiovascular disease, diabetes, and diabetes. [13][14][15][16][17][18][19][20][21][22][23][24][25][26] In the current study, the authors applied crosssectional study that explore the association between Body Mass Index (BMI) and sleep pattern among undergraduate female students of health colleges in Qassim University.…”
Section: Introductionmentioning
confidence: 99%